Systematic Literature Review (SLR): CIRC Learning Model on Reading Comprehension Skills in Indonesian Language Courses in Elementary School - Fakhriyah, Fina; Ilmi, Alfi Muzaroatul; Zulfia, Shabrina Khilda; Febbilla, Rona Fristi; Ismaya, Erik Aditia (International Journal of Educational and Psychological Sciences, 2024)
The CIRC (Cooperative Integrated Reading and Composition) learning method is a method that supports students in developing comprehensive reading skills and provides benefits for students to understand learning material. This study aims to conduct a literature review related to the CIRC learning model on students' reading comprehension skills. The research method used in this study is the SLR (Systematic Literature Review) method. Data collection is done by documenting all articles that have similar research in the research report. The articles used in this study were 4 national journal articles obtained from the Google Scholar database using the Publish or Perish application. The use of the CIRC learning model can be developed by teachers as a learning model to improve students' reading comprehension results.